Lumbalgia asociada a la actividad laboral en conductores de transporte público pesado de la ciudad de Loja, periodo 2015. - Chalán Veintimilla, Liliana Estefanía (2016)
Drivers of heavy public transport are people highly susceptible to back pain due to risk factors that may not be avoided but it could be limited improper biomechanics of the position when driving, thus constituting a health and socioeconomic first order problem, for the loss of working days and cost of treatment. Given its importance it arose establish the association between low back pain and work activities in the drivers of heavy public transport, to identify the risk factors that cause back pain and to establish the level of physical disability that exists as a result of low back pain in drivers of heavy public transport of Loja city, during the period 2015. It has been made a descriptive and transversal. Have been interviewed 147 drivers of heavy public transport in Loja city. Data were collected through a survey and Oswestry scale made face to face. The results obtained that low back pain is present in all drivers (100%), affecting between 20 and 40 years (68%). Among the predisposing risk factors were IMC, seniority, workload, sport, stress, sleep, driving posture, self-medication. Accounting for 54% of moderate functional limitations Keywords: low back pain, drivers, risk factors, Oswestry scale